2024
DOI: 10.1371/journal.pone.0298750
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gender roles, motherhood beliefs and mental health

Maribel Delgado-Herrera,
Anabel Claudia Aceves-Gómez,
Azalea Reyes-Aguilar

Abstract: Gender roles, as social constructs, play a significant role in shaping individuals’ beliefs and attitudes, influencing various aspects of life, including perceptions and expectations surrounding motherhood. These beliefs, acquired through culture and society, can have an impact on our mental well-being. This research consists of three independent studies conducted in the Mexican population. In the first and second studies, we extended the Attitudes Towards Gender Roles Scale and Motherhood Beliefs Scale and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
(89 reference statements)
0
0
0
Order By: Relevance
“…Beyond Sustainable Development Goal 5, gender equality is also necessary to achieve other United Nations goals, including Goal 3 to "ensure healthy lives and promote well-being for at all ages" (Langer et al 2015;Manandhar et al 2018;Weber et al 2019) and other goals that affect health outcomes (Manandhar et al 2018). Research has found differences between men and women on some health indicators, and there is evidence that the social roles traditionally ascribed to women and men are relevant to gender differences in health and well-being (Delgado-Herrera et al 2024;Matud 2017;Matud et al 2022Matud et al , 2023. Epidemiologic surveys have consistently documented differences between men and women in mental disorders, including higher rates of externalizing and substance use disorders among men than women and higher rates of anxiety and mood disorders among women than men (Seedat et al 2009;Boyd et al 2015), although a substantial narrowing of intercohort differences in major depression was found related to changes in traditional female gender roles (Seedat et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond Sustainable Development Goal 5, gender equality is also necessary to achieve other United Nations goals, including Goal 3 to "ensure healthy lives and promote well-being for at all ages" (Langer et al 2015;Manandhar et al 2018;Weber et al 2019) and other goals that affect health outcomes (Manandhar et al 2018). Research has found differences between men and women on some health indicators, and there is evidence that the social roles traditionally ascribed to women and men are relevant to gender differences in health and well-being (Delgado-Herrera et al 2024;Matud 2017;Matud et al 2022Matud et al , 2023. Epidemiologic surveys have consistently documented differences between men and women in mental disorders, including higher rates of externalizing and substance use disorders among men than women and higher rates of anxiety and mood disorders among women than men (Seedat et al 2009;Boyd et al 2015), although a substantial narrowing of intercohort differences in major depression was found related to changes in traditional female gender roles (Seedat et al 2009).…”
Section: Introductionmentioning
confidence: 99%